Die toepassing en gebruik van finansiele verhoudingsgetalle: 'n Verkenningstudie - J. K. Bosch; A. P. Du Plessis (South African Journal of Business Management, 1994)
– In this article the de facto use of financial ratios is reported on. To identify meaningful financial ratios, information was obtained from 166 enterprises on the use of financial ratios. The Likert scale was used to establish the frequency of use of the following categories of financial ratios, namely return on assets, income margins, capital turnover, solvency and ratios derived from the cash flow statement. In total, 41 financial ratios were submitted to the respondents. The most important findings were: Income margins are by far the group ratios with the highest frequency of use along with the debtors collection period. Further, with the help of a multiple analysis of variance, it was established that the main activities and size of respondents had no influence on the use of specific categories of financial ratios. Finally, the findings of a factor analysis indicated noticeable similarities between theoretical groupings of financial ratios and the results of the empirical study.
Keywords: 650